Growing (up) at work: Industrial placements and soft skill development among business students (Journal of Applied Learning and Teaching, 2025)
This paper offers an analysis of soft skill acquisition and development in the context of work placements, using a series of semi-structured interviews to offer a qualitative exploration of the placement experiences of business students. The paper chooses as its focus five key soft skills sought by graduate employers: 1) communication, 2) teamwork, 3) problem-solving, 4) time management and 5) creativity, and examines their development in the placement context. It highlights the benefits of work placements while acknowledging limitations and impediments. Recommendations for students, universities and placement employers are offered.